Model Predictive Controllers With Capacitor Voltage Balancing for a Single-Phase Five-Level SiC/Si Based ANPC Inverter - Najjar, Mohammad; Shahparasti, Mahdi; Heydari, Rasool; Nymand, Morten (IEEE, 2021)
Employing both high bandwidth (HBW) controller and wide bandgap (WBG) devices in the structure of converters improve the system size, performance, and efficiency. In this paper, HBW model predictive controllers (MPCs) are proposed, with both fixed and unfixed switching frequencies, to control a single-phase five-level hybrid active neutral-point-clamped (ANPC) inverter. A hybrid modulation technique is considered in this paper, in which some of the switches are modulating with high frequency. Therefore, Silicon-Carbide (SiC) MOSFETs are employed in the converter structure to increase the switching frequency and consequently reduce the filter size and increase converter power density. To have the functionality of multilevel output voltage, some restrictions are defined in the adopted MPC with unfixed switching frequency. In the MPC with the constant switching frequency, predefined switching sequences are employed for all sectors. Moreover, to control the neutral point (NP) voltage, the applied times of both small voltage vectors are sets through a cost function. Finally, the simulation and experimental results prove the ability of both proposed methods to control the voltages of the load and NP.
Keywords: Model predictive control; cost function; DC-AC converters; multilevel converter; voltage control; fi=Sähkötekniikka|en=Electrical Engineering|